2022
DOI: 10.1111/ene.15418
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐6‐phosphate dehydrogenase deficiency and intracranial atherosclerotic stenosis in stroke patients

Abstract: Background and purpose Intracranial atherosclerotic stenosis (ICAS) is a major cause of stroke in Asian countries. Glucose‐6‐phosphate dehydrogenase (G6PD) deficiency, a hereditary enzyme defect prevalent in Asian countries, has been associated with atherosclerotic cardiovascular disease and worse poststroke outcomes. However, the impact of G6PD deficiency on ICAS remains unclear. We aimed to compare the risk of ICAS in stroke patients with and without G6PD deficiency in a Chinese cohort. Methods We prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Consistent with our results, it has been demonstrated that ischemia-reperfusion can induce the elevation of the pentose phosphate pathway and associated G6PD activation, which may exhibit a neuroprotective effect via the phosphorylation of heat shock protein 27 ( Yamamoto et al, 2018 ). Furthermore, a recent study suggested that G6PD deficiency leads to poor prognosis and relatively high death rate in patients with cerebral ischemia ( Ou et al, 2020 ; Li et al, 2022 ). Moreover, accumulation of G6P caused by metabolic stress could be redirected from glycolysis into the pentose phosphate pathway to generate NADPH, thus leading to the activation of mTOR, which is greatly involved in neurogenesis ( Lipton and Sahin, 2014 ; Takei and Nawa, 2014 ; LiCausi and Hartman, 2018 ; Karlstaedt et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, it has been demonstrated that ischemia-reperfusion can induce the elevation of the pentose phosphate pathway and associated G6PD activation, which may exhibit a neuroprotective effect via the phosphorylation of heat shock protein 27 ( Yamamoto et al, 2018 ). Furthermore, a recent study suggested that G6PD deficiency leads to poor prognosis and relatively high death rate in patients with cerebral ischemia ( Ou et al, 2020 ; Li et al, 2022 ). Moreover, accumulation of G6P caused by metabolic stress could be redirected from glycolysis into the pentose phosphate pathway to generate NADPH, thus leading to the activation of mTOR, which is greatly involved in neurogenesis ( Lipton and Sahin, 2014 ; Takei and Nawa, 2014 ; LiCausi and Hartman, 2018 ; Karlstaedt et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%